2022
DOI: 10.3390/su142114068
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Financial Aid Systems on Student Academic Development in Higher Education in China

Abstract: The main purpose of this paper is to analyze the relationship between the multiple mixed financial aid systems and the academic development of college students in Chinese higher education. Under the assistance of National Student Financial Aid Center of China, this study used sample data from the questionnaire survey conducted among students in 11 colleges and universities, and used logistic regression analysis based on human capital theory and student development theory to investigate the effects of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The study found that the proportion of students enrolled in tertiary education had a significant positive effect on economic growth, while the proportion of students enrolled in secondary education had a significant negative impact on economic growth. Meanwhile, Qi et al [ 47 ] investigated the link between the academic growth of college students in Chinese higher education and various mixed financial aid programs. The study used a logistic regression model on data collected from a questionnaire survey given to students at 11 colleges and universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that the proportion of students enrolled in tertiary education had a significant positive effect on economic growth, while the proportion of students enrolled in secondary education had a significant negative impact on economic growth. Meanwhile, Qi et al [ 47 ] investigated the link between the academic growth of college students in Chinese higher education and various mixed financial aid programs. The study used a logistic regression model on data collected from a questionnaire survey given to students at 11 colleges and universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rab et al, however, stated that more research needs to be conducted on the relationship between bursary satisfaction and learning performance [18]. In another study, Qi et al [19] investigated the impact of two types of financial aid systems, government-sponsored and university-based financial aid, on student academic achievement and career development. The research method was a survey questionnaire distributed to 1000 undergraduate students in four Chinese universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The selection of academic growth metrics for sponsored college students now relies heavily on human capital factors. Academic performance indicators primarily evaluate the essential components of a person's human capital, which provides a theoretical framework for assessing how financial assistance affects the human capital of college students (Qi, Ma & Ji, 2022).…”
Section: Financial Aid As a Financing Modelmentioning
confidence: 99%